2009
DOI: 10.4081/rt.2009.e44
|View full text |Cite
|
Sign up to set email alerts
|

Cervical intramedullary schwannoma: a case report and review of the literature

Abstract: Intramedullary schwannomas unrelated with neurofibromatosis are uncommon tumors, but if correctly diagnosed and properly treated they may have a good prognosis.They have a wide range of clinical presentations, commonly presenting as a slowly progressive motor or sensory syndrome. We present a case report of a patient without neurofibromatosis with a surgically treated cervical intramedullary schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…1 Intramedullary schwannoma is more frequently found in males than females (male:female = 3:1). 10 The fourth decade of life is the mean age of onset of the symptoms. 11 Pyramidal symptoms manifest most commonly and are followed by sensory disturbances and sphincter malfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Intramedullary schwannoma is more frequently found in males than females (male:female = 3:1). 10 The fourth decade of life is the mean age of onset of the symptoms. 11 Pyramidal symptoms manifest most commonly and are followed by sensory disturbances and sphincter malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…7 In some cases, it has been reported that muscular fasciculations were the first clinical manifestation. 10 The time between the beginning of the symptoms until diagnosis was almost always lengthy, with a mean of 28.2 months (range: 6 weeks to 12 years). 7 Intramedullary schwannoma has three types based upon the lesion's location in the cross-sectional area of the spinal cord: central, surfacing, and dumbbell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Kernohan was recognized as the first neurosurgeon to report an IS in 1952, Penfield had reported this in 1932. [ 3 4 ] IS are rare, accounting for 0.3% of all primary spinal cord intramedullary neoplasms. [ 2 ] The most common location for IS is the cervical spine (63%) as in our case, followed by thoracic and lumbar levels.…”
Section: Discussionmentioning
confidence: 99%
“…As most of benign tumors, their presence is suspected by the onset of neurological signs in a slow-growing fashion caused by vascular or nervous conflicts. [2620] Spontaneous intracranial hemorrhage occurs in 3.9% of all brain tumors,[27] especially in aggressive ones, such as metastatic tumors or malignant gliomas. Apart from high-vascularized tumors, as choroid plexus papillomas and pituitary adenomas, spontaneous intracranial hemorrhage associated with a benign lesion is an even more uncommon condition.…”
Section: Introductionmentioning
confidence: 99%